Impact of a 'vegetables first' approach to complementary feeding on later intake and liking of vegetables in infants : a randomised controlled trial : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Nutritional Science at Massey University, Albany, New Zealand - Rapson, Jeanette (Massey University, 2021)
Background: Most children worldwide do not meet vegetable intake recommendations, which has implications for health, including an increased risk of obesity and chronic diseases later in life. A ‘vegetables first’ approach to complementary feeding has emerged as a promising strategy to promote vegetable consumption in children. This approach prioritises vegetables as first foods, capitalising on young infants’ willingness to try new foods and establish food preferences that comprise healthy eating. While some authorities have started to encourage the introduction of vegetables first, more longitudinal randomised, controlled studies are needed to strengthen the evidence-base. In addition, there is a concern that a focus on vegetables as first foods may negatively impact infant iron status, which needs to be addressed. Aims and objectives: The overall aim of this study was to determine whether exposure to vegetables-only during the first four weeks of complementary feeding increases later vegetable intake and liking, compared to a control group which includes both fruit and vegetables. The primary objective was to examine whether providing vegetable-only first foods results in higher intake of vegetables at 9 months of age, compared to a control. Secondary objectives were to examine infants’ acceptance of vegetable-only first foods, to assess whether intervention effects are maintained at 12 months of age, and to describe the iron status of infants who had participated in the trial. Methods/Design: In this longitudinal randomised, controlled, parallel-group study, 117 Auckland mother-infant dyads, received either vegetables-only (veg-only, n = 61) or a combination of fruit and vegetables (control, n = 56) for a duration of four weeks, starting from the first day of complementary feeding at around 4–6 months of age. At 9 months of age all infants were offered target vegetables at home: broccoli (day 1), spinach (day 2) and pear (day 3). At 12 months of age, mothers completed infant feeding questionnaires only. The primary outcome measure was intake (grams) of vegetables at 9 months of age. Additional food acceptance variables were mother-rated liking (5-point Likert scale), frequency of positive/negative behaviours (%), rate of eating (grams/min), rate of acceptance (video coding) and daily intake/preferences of fruit and vegetables (food frequency/liking questionnaires). Infants’ iron status (n = 75) was assessed at baseline, post-intervention and 9 months of age via capillary blood samples. Independent t-tests and Mann-Whitney tests were performed for the primary analysis. Demographic data was collected at baseline via an online questionnaire, and written consent obtained from all participants. Results: Of those who completed the 4-week intervention, 108 (92 %) provided intake data needed for the primary analysis at 9 months of age (veg-only, n = 56; controls, n = 52). Most (> 90 %) mothers had a university qualification or higher and were European ethnicity with adequate access to food. Intake of the target vegetables at 9 months was significantly higher among veg-only infants than controls: median (25th, 75th percentile) for broccoli was 47.0 (27.0, 72.0) vs 30.0 (16.0, 62.0) grams, P = 0.024, respectively; spinach was 37.0 (19.0, 55.0) vs 24.0 (12.0, 41.0) grams, P = 0.028, respectively. Daily vegetable intake was also significantly higher: veg-only group, 86.3 (52.5, 146.3) grams vs controls 67.5 (37.5, 101.3) grams, P = 0.042. Veg-only infants consumed the target vegetables at a faster rate (broccoli, P < 0.001; spinach, P = 0.004) and showed greater acceptance than controls (all target vegetables P = 0.018). Fruit intake (target and daily) was similar, as were all other acceptance variables. At 12 months of age (n = 107), these effects were maintained as daily vegetable intake was 20 % higher in the veg-only group, than controls (P = 0.021); daily fruit intake and liking of vegetables and fruit remained similar. With respect to secondary outcomes, intake, rate of eating and liking of the study foods during the 4-week intervention were similar between groups and increased significantly between week one and four (all P < 0.001). Frequency of negative behaviours in response to study foods in both groups significantly decreased over time (both P < 0.001) while positive behaviours did not change (veg-only P = 0.07; control P = 0.147). In terms of iron status, most were iron sufficient at baseline (93 %) and at 9 months of age (92 %). Conclusion: Providing vegetables as first foods increased vegetable intake at 9 months of age, and may be an effective strategy for improving child vegetable consumption and developing a preference for vegetables in infancy. Meanwhile, vegetable-only first foods were well-accepted and iron status maintained, which may be of encouragement to parents. However, given limited generalisability, more research investigating ways to support families in feeding vegetables as first foods at a population level is warranted.
Figures are reused with permission, or under a Creative Commons licence.
Keywords: Infants; Nutrition; Vegetables; 321004 Nutritional science